197k views
18 votes
Solve each system using the elimination method
4x-y=-2
2x+y=2

User ZombieTfk
by
5.3k points

1 Answer

8 votes

Answer:


\left \{ {{x=0} \atop {y=2}} \right.

Step-by-step explanation:
\left \{ {{4x-y=-2} \atop {2x+y=2}} \right.

Add the two equations


4x-y+(2x+y)=-2+2

Remove parentheses


4x-y+2x+y=-2+2

Cancel one variable


4x+2x=-2+2

Apply the Inverse Property of Addition


4x+2x=0

Combine like terms


6x=0

Divide both sides by the equation by the coefficient of variable


x=0

Substitute into one of the equations


2*0+y=2

Apply Zero Property of Multiplication


y=2

The solution of the system is


\left \{ {{x=0} \atop {y=2}} \right.

I hope this helps you

:)

User Tristen
by
5.0k points